2022
DOI: 10.1038/s41598-022-18996-x
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids’ treatment impairs the medium-term immunogenic response to SARS-CoV-2 mRNA vaccines in Systemic Lupus Erythematosus patients

Abstract: Limited data exists on SARS-CoV-2 sustained-response to vaccine in patients with rheumatic diseases. This study aims to evaluate neutralizing antibodies (nAB) induced by SARS-CoV-2 vaccine after 3 to 6 months from administration in Systemic Lupus Erythematosus (SLE) patients, as a surrogate of sustained-immunological response. This cross-sectional study compared nAB titre of 39 SLE patients and 37 Healthy individuals with no previous SARS-CoV-2 infection, who had all received a complete regimen of a mRNA SARS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Immune responses to SARS-CoV-2 vaccines involve both humoral and cellular components of adaptive immunity. Viral infections trigger type I IFN production as well as B cell activation, two mechanisms frequently altered in SLE patients and, hence, likely to interfere in their immunological response to vaccines [ 53 ].…”
Section: Pediatric Sle and Covid-19 Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Immune responses to SARS-CoV-2 vaccines involve both humoral and cellular components of adaptive immunity. Viral infections trigger type I IFN production as well as B cell activation, two mechanisms frequently altered in SLE patients and, hence, likely to interfere in their immunological response to vaccines [ 53 ].…”
Section: Pediatric Sle and Covid-19 Vaccinesmentioning
confidence: 99%
“…In contrast, Mehta et al reported that in SLE patients, the efficacy of COVID-19 vaccination is lower than in the general population, especially for those on MMF, RTX, GC and inactivated vaccines [ 16 ]. Similarly, Garcia-Cireira et al reported that GCs and Rituximab use had a negative influence on medium-term response of SLE patients to SARS-CoV-2 mRNA vaccines, while HCQ use had no impact on nAB levels, compared to control [ 53 ]. In contrast, Zheng et al reported that GCs in low doses had negligible effect on vaccine immunogenicity, while the results in HCQ and Rituximab use were close to ones reported by Garcia-Cereira et al [ 21 , 53 ].…”
Section: Pediatric Sle and Covid-19 Vaccinesmentioning
confidence: 99%
“…Humoral and cellular immune responses to COVID-19 in patients undergoing GC therapy show contradictory results. A recent study on patients with SLE concludes that the medium-term response of these patients to the SARS-CoV-2 vaccination may be compromised by GC use and by other prescribed treatments aimed to control the severity of the disease, such as rituximab, identifying the GC therapy as the factor most associated with declining levels of neutralizing antibodies induced by the vaccine [ 34 ]. On the contrary, another study concludes that COVID-19 vaccines are immunogenic in patients receiving immunosuppression, when assessed by a combination of serology and cell-based assays, despite the response being impaired compared to healthy individuals [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…In patients with SLE, several studies have established that mRNA COVID-19 vaccines are well tolerated, not associated with an increased risk of flares, but associated with a lower level of IgG anti-Spike Abs in association with a reduction of naïve B cell precursors at baseline [ [27] , [28] , [29] ]. The latter point is consistent with our report that the early stage of the humoral response is affected, which provides an argument to interrupt anti-metabolite drugs in the 2 weeks following COVID-19 vaccination as recently suggested [ 30 ].…”
Section: Discussionmentioning
confidence: 99%